Documentação pedagógica enquanto um exercício de sensibilização: do protagonismo das crianças ao olhar atento do educador - Camargo, Gabrielle Augusta Silva de (Universidade Federal de São Carlos, 2019)
This undergraduate thesis investigates the pedagogical documentation as an essential element to Early Childhood Education, allowing teachers being more critics with their practices, valuing more the children, their learnings, and different childhoods. During 2018 and 2019, critical thoughts were accomplished about the author own practice with a group of 18 children, using photos, drawings and speeches registers to compose the research. Teachers’ critical thoughts can contribute to the development of the children identities, helping them to be more autonomies and creativities. The main goal of this research is to know different ways to create the pedagogical documentation and to document practices, comprehending the documentation in its complexity, studying and extending meaningful knowledge to the pedagogical practice, that craves for the legitimacy of the children’s rights, helping the improvement of the public education and the construction of a fairer society. This paperwork came from a bibliographic and pedagogical research (LANKSHEAR & NOBEL, 2008), making an effort to establish praxeological knowledge (FOCHI, 2019) through dialogues between theory and practice, dialogical articulation between context and individuals, understanding this movement as something essential to Kindergarten, to teachers’ practices, children and their childhoods.
Pedagogical documentation as an awareness-raising exercise: from children´s protagonism to teacher’s attentive look
Keywords: Documentação pedagógica; Pedagogical documentation; Educação Infantil; Early Childhood Education; Pesquisa pedagógica; Pedagogic research; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO